Haematological Study for Women in Two Villages in Najaf Governorate - Majeed, Nabeel Sahib; Mahdi, Liwaa Hussein (Al-Qadisiyah Journal of Pure Science, 2017)
The present investigation was an attempt to obtain profiler of a major public health problem among women in the reproductive age group. On the basis of prevalence studies that ( 20 – 30 % ) of women suffer from anaemia . The mean age of the women was ( 26.54 ± 8.45 ) years . The mean haemoglobin and PCV values were ( 12.71 ± 4.09 ) and ( 37.99 ± 4.47 ) respectively . Among the ( 610 ) women included in the study , ( 96 ) were pregnant at the time of the survey . The prevalence rates of anaemia among the pregnant and non-pregnant women based upon the haemoglobin values were estimated to be ( 36 - 46 % ) and ( 25 – 48 % ) respectively . The difference between the two values was found to be highly significant ( p < 0.001 ) . The corresponding haemotocrit values for the two groups were ( 35.72 ± 5.31 ) and ( 38.42 ± 4.30 ) respectively . When the relationship of two factors of age and parity was examined , it was found that there was a decline in haemoglobin level with increase in parity . Blood film morphology : The hypochromic microcytic type of anaemia indicative of iron deficiency , accounted for ( 63 % ) of the cases where as among the nonpregnant women this was found to exist to the extent of ( 46.3 % ) . Haemoglobin genotype among the ( 610 ) women ( 108 ) ( 17.7 % ) showed evidence of sickle cell disease , a good majority ( 16 % ) carried the sickle cell anaemia . It was seen that in the case of subject with ss gene , the haemoglobin values ranged from ( 8.6 – 11.5 ) ( mean 9.65 ± 0.9 grams % ) where as those with As gene had heamoglobin values ranging from ( 8.5 – 16.2 ) ( mean 12.17 ± 1.65 grams % ) .